Ceramide Regulates Anti-Tumor Mechanisms of Erianin in Androgen-Sensitive and Castration-Resistant Prostate Cancers - Trapika, I Gusti Md Gde Surya C.; Liu, Xin Tracy; Chung, Long Hoa; Lai, Felcia; Xie, Chanlu; Zhao, Yang; Cui, Shaohui; Chen, Jinbiao; Tran, Collin; Wang, Qian; Zhang, Shubiao; Don, Anthony S.; et al. (Frontiers in Oncology, 2021)
Prostate cancer is the second most prevalent malignancy worldwide. In the early stages, the development of prostate cancer is dependent on androgens. Over time with androgen deprivation therapy, 20% of prostate cancers progress to a castration-resistant form. Novel treatments for prostate cancers are still urgently needed. Erianin is a plant-derived bibenzyl compound. We report herein that erianin exhibits anti-tumor effects in androgen-sensitive and castration-resistant prostate cancer cells through different mechanisms. Erianin induces endoplasmic reticulum stress-associated apoptosis in androgen-sensitive prostate cancer cells, triggering prosurvival autophagic responses, as inhibition of autophagy predisposes to apoptosis. In contrast, erianin fails to induce apoptosis in castration-resistant prostate cancer cells. Instead, it results in cell cycle arrest at the M phase. Mechanistically, C16 ceramide dictates differential responses of androgen-sensitive and castration-resistant prostate cancer cells to erianin. Erianin elevates C16 ceramide level in androgen-sensitive but not castration-resistant prostate cancer cells. Overexpression of ceramide synthase 5 that specifically produces C16 ceramide enables erianin to induce apoptosis in castration-resistant prostate cancer cells. Our study provides both experimental evidence and mechanistic data showing that erianin is a potential treatment option for prostate cancers.